Willingness to pay and consumer preferences for organic lettuce (Lactuca sativa L.) - A. Cerda, Arcadio; Y. García, Leidy; I. Viscay, Angela; M. López, Beatriz (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Global production of organic products has grown significantly due to increased environmental awareness and healthier lifestyles. However, vegetable growers often lack relevant information about people’s preferences and willingness to pay (WTP) for such products. This difficulty is even more pronounced in developing countries, as Chile, mainly due to the low demand increase for organic products. This research aims to analyze preferences and WTP for Chilean organic lettuce. To obtain the WTP, the contingent valuation (CV) method and conjoint analysis (CA) was applied. The data were obtained from a cross-sectional survey using a representative sample of 416 subjects from the Maule region, Chile, stratified by income level. The results showed that subjects were willing to pay a premium of 26.72 % and 52.83 % for an organic head of lettuce compared to conventionally grown products, according to CA and CV methods, respectively. These results show a strong preference for organic products. Furthermore, the CA method indicated that the organic variety of Lactuca sativa L. var. crispa L., at its lowest observed price, was the consumer’s product of choice. Finally, the main reasons to consume this type of product are, firstly, its higher quality, followed by its taste or smell, and finally, it has better nutritional contents. Therefore, lettuce growers can use the estimated premium price as a reference when making decisions about production and pricing.